Catatan Evaluatif Tri Lustrum Otonomi Khusus Aceh - Eduardo Edwin Ramda (Ministry of Home Affairs, 2022)
Tri lustrum implementation of special autonomy in Aceh requires evaluation of all dimensions of regional autonomy. Evaluation notes are important as a basis for developing a special autonomy policy framework in the future. This study aims to present a corrective note on the implementation of special autonomy in Aceh Province and its regencies and cities. This research uses a qualitative descriptive approach with literature study and spatial analysis methods. The novelty presented in this article is the presence of a multidimensional discussion of special autonomy to see the performance of Aceh over the past fifteen years. The urgency is the amount of the Special Autonomy Fund for the sixteenth year to the twentieth year, which is equivalent to 1% (one percent) of the ceiling of the National General Allocation Fund (DAU). Significant spatial changes have occurred in the last fifteen years in Aceh, although they are still slower than other areas in Sumatra. Another problem that arises in this study is the stagnant position of Aceh as a region that is not yet fiscally independent. The political dimension also shows that the people's political preference for local parties in Aceh has weakened. This study also highlights the absence of a standard reference regarding the division of authority between the Central Government, Aceh Government, and Regency/City Governments. In conclusion, special autonomy in Aceh has not been running optimally and requires reform of the Special Autonomy policy as a corrective effort to several problems presented in this study.